1987
DOI: 10.1530/acta.0.1140096
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin-(1-13) is a potent in vivo suppressor of vasopressin levels in the rat

Abstract: Intracerebroventricular administration of dynorphin-(1-13) inhibits dose-dependently plasma vasopressin level in normal as well as in water-deprived rats, whereas systemic (subcutaneous) administration of this opioid peptide is ineffective in this respect. Simultaneous subcutaneous, but not intracerebroventricular, administration of naloxone prevents the suppressive effect of dynorphin-(1-13) on plasma vasopressin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Hence, it seems that U50488H may inhibit AVP secre tion via the posterior pituitary. Meanwhile, it was reported that dynorphin, an endogenous K-opioid agonist, binds to some opioid receptors in the neurohypophysis [9], and dynorphin, per se, was reported to exert a potent sup pressive action on plasma AVP [10]. These observations also support our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, it seems that U50488H may inhibit AVP secre tion via the posterior pituitary. Meanwhile, it was reported that dynorphin, an endogenous K-opioid agonist, binds to some opioid receptors in the neurohypophysis [9], and dynorphin, per se, was reported to exert a potent sup pressive action on plasma AVP [10]. These observations also support our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies demonstrated diureses or a decrease in vasopressin release by K-agonists injected into the ventri cle (14)(15)(16). This is not consistent with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…Met-enkephalin is reported to show di ureses by intracerebroventricular injection and anti diureses by microinjection into nuclei (6,33). 2) In the studies for the diureses or decrease in vasopressin release by the K-agonists, conscious and non-hydrated (14 16), water-deprived (14), hydrated (16) or angiotensin II stimulated (15) rats are used. Basal vasopressin level in the plasma under these conditions will be higher than that under the ethanol-anesthetized, ethanol-infused and hydrated condition in the present study, although under the present condition, it is possible to produce diureses by some drugs (this study, ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, i.c.v. injection of dynorphin or bremazocine, K-agonists, produces the oppo site effects (16,17). Also, we have reported the antidiuret ic effect induced by microinjection of morphine or fen tanyl into the nuclei (18,19).…”
mentioning
confidence: 93%